Selective Suppression of Integrin-Ligand Binding by Single Molecular Tension Probes Mediates Directional Cell Migration - Han, Seong-Beom; Lee, Geonhui; Kim, Daesan; Kim, Jeong-Ki; Kim, In-San; Kim, Hae-Won; Kim, Dong-Hwee (Wiley-VCH Verlag, 2024)
Cell migration interacting with continuously changing microenvironment, is one of the most essential cellular functions, participating in embryonic development, wound repair, immune response, and cancer metastasis. The migration process is finely tuned by integrin-mediated binding to ligand molecules. Although numerous biochemical pathways orchestrating cell adhesion and motility are identified, how subcellular forces between the cell and extracellular matrix regulate intracellular signaling for cell migration remains unclear. Here, it is showed that a molecular binding force across integrin subunits determines directional migration by regulating tension-dependent focal contact formation and focal adhesion kinase phosphorylation. Molecular binding strength between integrin alpha(v)beta(3) and fibronectin is precisely manipulated by developing molecular tension probes that control the mechanical tolerance applied to cell-substrate interfaces. This data reveals that integrin-mediated molecular binding force reduction suppresses cell spreading and focal adhesion formation, attenuating the focal adhesion kinase (FAK) phosphorylation that regulates the persistence of cell migration. These results further demonstrate that manipulating subcellular binding forces at the molecular level can recapitulate differential cell migration in response to changes of substrate rigidity that determines the physical condition of extracellular microenvironment. Novel insights is provided into the subcellular mechanics behind global mechanical adaptation of the cell to surrounding tissue environments featuring distinct biophysical signatures.